The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c3lc50625h
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for label-free separation of circulating tumor cells: from historical foundations to recent developments

Abstract: Circulating tumor cells (CTCs) are malignant cells shed into the bloodstream from a tumor that have the potential to establish metastases in different anatomical sites. The separation and subsequent characterization of these cells is emerging as an important tool for both biomarker discovery and the elucidation of mechanisms of metastasis. Established methods for separating CTCs rely on biochemical markers of epithelial cells that are known to be unreliable because of epithelial-to-mesenchymal transition, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
154
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(158 citation statements)
references
References 109 publications
1
154
0
Order By: Relevance
“…We can deduce that, thanks to thick C-PDMS electrodes, DEP capture throughput can be increased while keeping a large capture yield. This yield is in the same order of magnitude as previously published works 42 where yield ranges from 60 to 96% and flow rates ranges from 6 ll/h to 1 ml/h.…”
Section: -9supporting
confidence: 74%
“…We can deduce that, thanks to thick C-PDMS electrodes, DEP capture throughput can be increased while keeping a large capture yield. This yield is in the same order of magnitude as previously published works 42 where yield ranges from 60 to 96% and flow rates ranges from 6 ll/h to 1 ml/h.…”
Section: -9supporting
confidence: 74%
“…Several reviews have discussed the various CTC enrichment and detection technologies (7,(9)(10)(11)(12). Table 1 presents an updated list of CTC assays that have been used to test patient samples within the past 5 years, along with their commercialization status.…”
Section: Ctc Enrichment and Detection Technologiesmentioning
confidence: 99%
“…[22][23][24] The capture, isolation and enrichment of non-adherent abnormal CTC are based on their difference from hematologic cells in size and biophysical deformities such as such as shape, stiffness and electrical polarizability. [13][14][15][16][17][18][25][26][27][28][29] Many studies have reported that tumor cells are larger in size as compared to hematologic cells and this difference accounts for the…”
Section: Introductionmentioning
confidence: 99%